Effect of Frusemide, Lactose, and Urea on Urinary Cell Loss. Issue 5626 (2nd November 1968) - Gent, A. E.; Taylor, J. F. N.; Brook, C. G. D.
Abstract : With the use of a staining method by which cells in the urine can be differentiated, the effect of oral frusemide, lactose, and urea on the rate of excretion of these cells was investigated in five healthy persons. It is shown that frusemide greatly increases the urinary excretion of red cells, white cells, and renal tubular cells. Similar though not so marked changes were produced by both lactose and urea. Possible reasons for the increased excretion of cells are discussed. One is that it may be the result of an increase in the rate of urinary flow.